(untitled) (Global Journal of Science Frontier Research, 2021)
Four major subjects in solar physics, the heating of the corona, the cause of the solar wind, the formation of sunspots and the cause of solar flares, are discussed on the basis of the electric current approach, a sequence of processes consisting of power supply(dynamo), transmission (currents/circuits) and dissipation(high coronal temperature, solar wind, sunspots and solar flares). This is because the four subjects have hardly been considered in terms of the electric current approach in the past, in spite of the fact that these subjects are various manifestations of electromagnetic processes. It is shown that this approach provides a new systematic way of considering each subject; (1) the long-standing issue of the coronal temperature, (2) the long-standing problem on the cause of the solar wind, (3)the presence of single spots(forgotten or dismissed in the past) and its relation to unipolar magnetic regions and (4) the crucial power/energy source and subsequent explosive processes of solar flares. The four subjects are obviously extremely complicated and difficult subjects, but it is hoped that the electric current approach might provide a new insight in considering the four subjects.